Predicting consequences of POP-induced disruption of blubber glucose uptake, mass gain rate and thyroid hormone levels for weaning mass in grey seal pups. (July 2021) - Bennett, Kimberley A.; Robinson, Kelly J.; Armstrong, Holly C.; Moss, Simon E.W.; Scholl, Georges; Tranganida, Alexandra; Eppe, Gauthier; Thomé, Jean-Pierre; Debier, Cathy; Hall, Ailsa J.
Graphical abstract: Highlights: Glucose uptake by blubber was a strong predictor of grey seal pup mass gain rate. POPs altered weaning mass through disrupted blubber function, thyroid hormones and mass gain. Greater POP-induced reductions in weaning mass were predicted in smaller pups. POP energy balance effects were mostly small but may exacerbate other stressors. Linking in vitro with in vivo data helps predict stressor impacts on energy balance. Abstract: Persistent organic pollutants (POPs) are endocrine disruptors that alter adipose tissue development, regulation and function. Top marine predators are particularly vulnerable because they possess large fat stores that accumulate POPs. However, links between endocrine or adipose tissue function disruption and whole animal energetics have rarely been investigated. We predicted the impact of alterations to blubber metabolic characteristics and circulating thyroid hormone (TH) levels associated with polychlorinated biphenyls (PCBs), polybrominated diphenyl ethers (PBDEs), and organochlorine pesticides (OCPs) on suckling mass gain and weaning mass in wild grey seal pups. Glucose uptake by inner blubber was a strong predictor of whole animal mass gain rate, which in turn, resulted in heavier weaning mass. Weaning mass was predicted to increase by 3.7 ± 1.59 (sem) %, through increased mass gain rate, in the absence of the previously reported suppressive effect of dioxin-like PCB (DL-PCBs) on blubber glucose uptake. PBDEs were, conversely, associated with faster mass gain. Alleviation of this effect was predicted to reduce weaning mass by 6.02 ± 1.86% (sem). To better predict POPs effects on energy balance, it is crucial to determine if and how PBDEs promote mass gain in grey seal pups. Weaning mass was negatively related to total T3 (TT3) levels. A 20% (range = 9.3–31.7%) reduction in TT3 by DL-PCBs partially overcame the effect of DL-PCB -mediated reduction in blubber glucose uptake. Overall, DL-PCBs were thus predicted to reduce weaning mass by 1.86 ± 1.60%. Organohalogen impacts on whole-animal energy balance in grey seal pups appear to partially offset each other through opposing effects on different mechanisms. POP effects were generally minor, but the largest POP-induced reductions in weaning mass were predicted to occur in pups that were already small. Since weaning mass is positively related to first-year survival, POPs may disproportionately affect smaller individuals, and could continue to have population-level impacts even when levels are relatively low compared to historical values. Our findings show how in vitro experiments combined with measurements in vivo can help elucidate mechanisms that underpin energy balance regulation and help to quantify the magnitude of disruptive effects by contaminants and other stressors in wildlife.